The returns to computer use revisited, again - Benoît Dostie; Rajshri Jayaraman; Mathieu Trépanier (Institute for the Study of Labor (IZA), 2006)
Using North American data, we revisit the question first broached by Krueger (1993) and re-examined by DiNardo and Pischke (1997) of whether there exists a real wage differential associated with computer use. Employing a mixed effects model to correct for both worker and workplace unobserved heterogeneity using matched employer-employee panel data, we find that computer users enjoy an almost 4 per cent wage premium over non-users. Failure to correct for the worker selection effect leads to a more than twofold overestimate of this premium, as does failure to correct for workplace unobserved heterogeneity.
Keywords: J30; J31; O30; 330; wage determination; computers; mixed models; linked employer-employee data